My Name is Nobody - Richardson, Matthew, 1990-, author (London : Penguin Books, 2018)
'PROOF THAT THE SPY GENRE IS FLOURISHING IN THE 21ST CENTURY' Guardian 'I know for certain that there is a mole somewhere within the intelligence services . . . His codename is Nobody . . .' Solomon Vine is a spy on a fast track to the top. But when a prisoner is shot in unexplained circumstances on his watch, only suspension and exile beckon. Three months later, MI6's Head of Station in Istanbul is violently abducted from his home. With the Service in lockdown, uncertain of who can be trusted, thoughts turn to the missing man's oldest friend: Solomon Vine. On the run and determined to clear his name, Vine tries to uncover the truth. But his investigation soon reveals that there's much more at stake than the life of a single spy... 'Compelling, intense and sharply authentic' James Swallow, bestselling author of Nomad 'A supremely confident debut' Daily Mail 'Authentic, mysterious, fraught with deception, betrayal, and uncertain allegiances' Jason Matthews, author of Red Sparrow 'Such a smart, pacey, twisty thriller. Tremendous!' C.J. Tudor, author of The Chalk Man.